Adaptasi Penerapan Nilai-Nilai Ajaran Islam Dalam Konteks Budaya Global - Alifia Saffanatus Fajri; Reka Ayu Adella (Purwadita : Jurnal Agama dan Budaya, 2022)
The purpose of this writing is to know the application of the value of Islamic teachings in global culture. The method used is library research, which is research that is studied through literature or literature studies. Based on the study of this article it can be concluded that there is a relationship of religion and modern culture, namely vertical to God and horizontal through social piety. Muslim thinkers and Islamic organizations also have an important role to produce quality human resources but still guided by the teachings of the Quran and Hadith. The tendency of multicultural culture can have a negative impact on Islamic values in society. For example, western culture and values are considered modern. While tradition, cultural and religious values are outdated. But the culture of globalization also provides opportunities in the application of religious values such as the easier communication and information between human beings, thus the transformation of the value of Islamic teachings is increasingly widespread.  Keywords: globalization, Islamic values, problems and strategies